Antimicrobial Activity of a Novel Cu(NO3)2-Containing Sol–Gel Surface under Different Testing Conditions - Daniela Toplitsch (MDPI AG, 2021)
In this study, assessment of the antimicrobial activity of a novel, plasma-cured 2.5% (w/v) Cu(NO3)2-containing sol–gel surface was performed. In contrast to state-of-the-art sol–gel coatings, the plasma curing led to a gradient in cross-linking with the highest values at the top of the coating. As a result, the coating behaved simultaneously hard, scratch-resistant, and tough, the latter due to the more flexible bulk of the coating toward the substrate. Further, the diffusion and permeation through the coating also increased toward the substrate. In our study, tests according to ISO 22196 showed antibacterial activity of the 2.5% (w/v) Cu(NO3)2-containing sol–gel surface against all bacterial strains tested, and we expanded the testing further using a “dry” evaluation without an aqueous contact phase, which confirmed the antimicrobial efficacy of the 2.5% (w/v) Cu(NO3)2-containing sol–gel surface. However, further investigation under exposure to soiling with the addition of 0.3% albumin, used to simulate organic load, led to a significant impairment in the antibacterial effect under both tested conditions. Furthermore, re-testing of the surface after disinfection with 70% ethanol led to a total loss of antibacterial activity. Our results showed that besides the mere application of an antimicrobial agent to a surface coating, it is also necessary to consider the future use of these surfaces in the experimental phase combining industry and science. Therefore, a number of tests corresponding to the utilization of the surface should be obligative on the basis of this assessment.